2010
DOI: 10.1007/s00220-010-1116-6
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Stability, Concentration, and Oscillation in Harmonic Map Heat-Flow, Landau-Lifshitz, and Schrödinger Maps on $${\mathbb R^2}$$

Abstract: We consider the Landau-Lifshitz equations of ferromagnetism (including the harmonic map heat-flow and Schrödinger flow as special cases) for degree m equivariant maps from R 2 to S 2 . If m ≥ 3, we prove that near-minimal energy solutions converge to a harmonic map as t → ∞ (asymptotic stability), extending previous work [11] down to degree m = 3. Due to slow spatial decay of the harmonic map components, a new approach is needed for m = 3, involving (among other tools) a "normal form" for the parameter dynamic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
100
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(111 citation statements)
references
References 21 publications
(61 reference statements)
7
100
0
4
Order By: Relevance
“…In particular, other type of blow up speeds can be produced by similar arguments by changing the tail of the initial data. A similar phenomenon was observed for global in time growing up solutions to the parabolic energy critical harmonic heat flow by Gustafson, Nakanishi and Tsai [7]. In [7], an explicit formula on the growth of the solution at infinity is given directly in terms of the initial data.…”
Section: Xxxvii-6supporting
confidence: 68%
See 2 more Smart Citations
“…In particular, other type of blow up speeds can be produced by similar arguments by changing the tail of the initial data. A similar phenomenon was observed for global in time growing up solutions to the parabolic energy critical harmonic heat flow by Gustafson, Nakanishi and Tsai [7]. In [7], an explicit formula on the growth of the solution at infinity is given directly in terms of the initial data.…”
Section: Xxxvii-6supporting
confidence: 68%
“…A similar phenomenon was observed for global in time growing up solutions to the parabolic energy critical harmonic heat flow by Gustafson, Nakanishi and Tsai [7]. In [7], an explicit formula on the growth of the solution at infinity is given directly in terms of the initial data. Continuums of blow up rates were also observed in pioneering works by Krieger, Schlag and Tataru [15], [16] for energy critical wave problems, see also Donninger and Krieger [3].…”
Section: Xxxvii-6supporting
confidence: 68%
See 1 more Smart Citation
“…Asymptotic stability of harmonic maps of topological degree |m| ≥ 4 under the Schrödinger flow is established in [Gustafson et al 2008]. The result is extended to maps of degree |m| ≥ 3 in [Gustafson et al 2010]. A certain energy-class instability for degree-1 solitons of (1-1) is shown in [Bejenaru and Tataru 2010], where it is also shown that global solutions always exist for small localized equivariant perturbations of degree-1 solitons.…”
Section: Introductionmentioning
confidence: 99%
“…The readers are referred to [1,2,13,18,19,26,29,33] for more details. Note that if |u 0 | = 1, it is easily to show that |u(t)| = 1 for all t ≥ 0.…”
Section: Introductionmentioning
confidence: 99%